Answer:
c
Explanation:
a) is wrong.
If A is a subset of B, then cardinality of (AUB) = cardinality B.
For example: A = {1}, B = {1,2,3} cardinality(A) = 1, cardinality(B) = 3.
AUB = {1,2,3} cardinality(AUB) = 3 = cardinality(B)
For the same reason as a), b) is wrong. If B is a subset of A, then the cardinality(AUB) = cardinality(A).
c) is right.
We have already seen that if a set A is a subset of a set B, then cardinality(AUB) = B.
Using A = {1} and B = {2,3}, cardinality(A) = 1, cardinality(B) = 2
Then AUB = {1,2,3} and cardinality(AUB) = 3 = cardinality(A)+cardinality(B)